School Belonging in Different Cultures: The Effects of Individualism and Power Distance - Cortina, Kai S.; Arel, Sari; Smith-Darden, Joanne P. (Frontiers in Education, 2017)
Limited evidence exists on how the larger cultural framework affects psychological processes related to schooling. We investigated how the cultural dimensions of individualism/collectivism and power distance influence the sense of school belongingness using Programme for International Student Assessment (PISA) 2003 survey data on 15-year-old students from 31 countries. Hierarchical linear model analysis indicated that power distance (i.e. hierarchical nature of social relationships) is a better predictor of school belongingness on the cultural level than individualism/collectivism. Accordingly, students living in cultures with high degree of power distance (particularly East Asian countries in these data) report lower school belongingness than students living in cultures with more lateral power relationships (Western countries). Positive teacher student relations and preference for cooperative learning environment predict higher school belongingness across cultures.